(untitled) (Research, Society and Development, 2021)
Introducion: Adolescence is a período marked by major biological, psychological and social changes, in which there are conflicts and weaknesses, wich can cause changes in mental health and psycho-emotional well-being. Objective: to learn the adolescentes experiences pf non-suicidal self-harm and suicidal behavior and related weaknesses. Methodos: a descriptive study with a qualitative approach, carried out with 53 adolescentes, from 12 to 17 years old. Data collection was carried out from the Pichon-Rivière Operating Groups, reading a triggering situation regarding non-suicidal self-harm and suicidal behavior and guiding questions. The theoretical framework for the analysis of thematic content of Bardin was used, interpreted by the framework of the Life Skills Model. Results: it is learned that non-suicidal self-injury is an escape from psycho-emotional suffering through physical pain and suicidal behavior is an attempt to end suffering, which would end with life. They reported problems with family, school and peers, who do not provide necessary support for their emotional well-being. Appear permeated by judgment and lack of empathy, some tried to cope by exposing themselves to other risks, such as alcohol / drugs, violence and social networks. Conclusion: it is clear that school adolescents with intense suffering experience non-suicidal self-injury and suicidal behavior directly or indirectly, so it is necessary that education and health professionals, especially nurses, be effective in conducting strategies aimed at preventing and promoting adolescent mental well-being.